Comparative Analysis of Total Station and Mobile Base Station Accuracy in Determining Land Plot Volume (Case Study of Metland Land Plot) - Abadiyah, Siti; Ramadhan, Fajar (Universitas Ibn Khaldun Bogor, 2025)
Measurement of land using extraterrestrial methods has developed quite rapidly due to the increasingly sophisticated measuring instruments used in measurements using these methods. The problem lies in the long baseline that causes the rover to take a long time to reach a fixed solution. Mobile Base Station can be used as an alternative solution to the problem because it can bring the base station closer to the measurement location, thus increasing measurement efficiency. The purpose of this study was to determine the accuracy of the aspects of coordinate differences and differences in land area and to determine the efficiency of land area measurement time using Mobile Base Station South Type Galaxy G1. The research method used is a comparative experiment with a quantitative approach. The samples selected were 89 residential land parcels in 1 (one) block. Sample measurements were carried out twice, namely using Mobile Base Station South Type Galaxy G1 with extraterrestrial methods and using Total Station as comparison data. The analysis used is the t test with a significance level (α) of 5%. The results showed that there was a significant difference between the coordinates of the land plot measured by the Mobile Base Station and the coordinates measured by the Total Station. The length of time needed to complete the work in this study with the Total Station tool is 585 minutes or or 9 hours 45 minutes and for the Mobile Base Station South tool it takes 476 minutes or 7 hours 56 minutes. And based on the results of the calculation of the time efficiency of these measurements that have been carried out combined with the time efficiency with the implementation of measurements during practical work is 37.24%.